MEMBANGUN ETOS KERJA GURU - Syarifuddin Syarifuddin (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2018)
In trying to develop teacher work ethos is feeling getting fair treatment: honest, healthy, just and etc. Teachers have to be aware that they are competent people. It means that they have to give big contribution for certain activity till the progress in teaching happens.